Do Ukrainian firms benefit from FDI - Stefan H. Lutz; Oleksandr Talavera (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2003)
All countries are eager to attract as much foreign investments as possible. At the same time FDI may have not only positive, but also negative economic effects for receiving countries. Positive effects are associated with technology transfer, efficient allocation of resources, and training of domestic workers. However, the entry of foreign firms could, e.g., lead to a decrease of labor productivity at domestic firms, which is a negative effect. The main purpose of this paper is to estimate direct and indirect effects of FDI. First, we test for direct influence of foreign direct investments on firms' performance, where the latter is estimated alternatively as labor productivity and as exports. FDI notably increases both labor productivity and export volumes. Second, we look for spillover or indirect effects. There is statistical evidence that the levels of FDI in certain regional industries are associated with higher performance indicators of firms' not receiving FDI in those same regional industries.
Keywords: L1; L6; F2; 330; Foreign direct investment; firm performance; spillovers; Ukraine; Direktinvestition; Unternehmensentwicklung; Arbeitsproduktivität; Export; Spillover-Effekt; Schätzung